Correction to: Regional differences in baseline disease activity and remission rates following golimumab treatment for RA: results from the GO-MORE trial - Durez, Patrick; Pavelka, Karel; Lazaro, Maria Alicia; Garcia-Kutzbach, Abraham; Moots, Robert J; Amital, Howard; Govoni, Marinella; Vastesaeger, Nathan (Clinical rheumatology, 2018)
The original publication contains two areas which require correcting. None of these errors change the results or conclusions of the article, but the authors wish to highlight the areas of change to the reader.